PEMETAAN MEDIA TENTANG KONSEP DAN IMPLEMENTASI GREEN ACCOUNTING DI INDONESIA MENGGUNAKAN NVIVO - Dimas Trilaksono; Dina Alafi Hidayatin (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to analyze media mapping regarding the application of green accounting to corporate financial performance in Indonesia using NVivo software. This research employs a qualitative method based on literature reviews and media analysis. Data analysis techniques include mapping news article codes based on concepts, implementation, and impacts of green accounting on corporate financial performance; visualizing results with hierarchy diagrams; analyzing correlations between media articles; and identifying discussion trends through word clouds. The results reveal that the most frequently discussed topic in media articles is the basic concept of green accounting, stakeholder, while practical implementation is rarely highlighted. The study concludes that analysis using NVivo is effective in understanding green accounting discussion trends in media. The implications of this study provide strategic recommendations to enhance corporate and public literacy and awareness about the importance of green accounting adoption to support sustainable financial performance.